STEM Education Enhancement Through Effective Professional Development: A Comprehensive Program for Long-Term Growth - Maspul, Kurniawan Arif (Ruang Publikasi Ilmiah, 2024)
The necessity for effective professional development (PD) in STEM education is more intense than ever. Shorter PD programs, on the other hand, are frequently more feasible due to time restrictions. The study looks into the most successful ways of designing and implementing short-term PD programs that provide significant results. Short-term PD programs can deliver intense bursts of improvement by focusing on dynamic training, personalized learning routes, and ongoing support. This study looks at how these programs can help educators modify their methods and improve student learning results. Collaborative networks and communities of practice are also essential for maximizing the impact of short-term PD. The transformative benefits can spread throughout schools and districts by creating relationships and boosting collaboration. This study demonstrates the potential for brief, meaningful PD programs to transform STEM instruction. Educators are embracing brief yet transformative professional development sessions and observing the enormous impact they can have on the future of STEM education.